The algorithms of inferring three dimensional structure from three-view engineering drawings - Shen, Jun; Sadanada, R.; Bohez, Erik L.J.; The Government of Japan (Bangkok : Asian Institute of Technology, 1991)
A group of algorithms for automating three-dimensional object structure inferring from three-view engineering drawings are presented in this paper. The algorithms are general ones for reconstructing 3-D polygon objects with concave structures. The recovery procedure is that, first, identify all vertices and edges and store them in a central data structure. Then explain all co-planar vertices closer to the viewer to find visible faces. Finally, explain dashed lines as hidden faces of concave and infer all the other faces as default for the other missing views. Several demonstrating examples are given in the paper.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1991
Keywords: Engineering drawings -- Dimensioning